Lipid- and Polymer-Based Nanoparticle Systems for the Delivery of CRISPR/Cas9 - Ashok, Bhaargavi (J Drug Deliv Sci Technol, 2021)
The discovery of clustered regularly interspaced short palindromic repeat (CRISPR)/ CRISPR-associated (Cas) genome editing systems and their applications in human health and medicine has heralded a new era of biotechnology. However, the delivery of CRISPR therapeutics is arguably the most difficult barrier to overcome for translation to in vivo clinical administration. Appropriate delivery methods are required to efficiently and selectively transport all gene editing components to specific target cells and tissues of interest, while minimizing off-target effects. To overcome this challenge, we discuss and critic nanoparticle delivery strategies, focusing on the use of lipid-based and polymeric-based matrices herein.